Behavioral intention on tropical island tourism: assessing the destination image effect through mte and satisfaction - Wulandari, Gusti Ayu; Suryaningsih, Ika Barokah; Merinda, Shohibatun Nisa (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
East Java Province is a major driver of domestic tourism in Indonesia and has strong potential for developing its remote tropical islands. However, tourism growth in these areas is hindered by limited accessibility and inadequate infrastructure. This study examines how sustainable tourism can be promoted by analyzing the relationships among destination image, memorable tourism experiences (MTEs), tourist satisfaction, and behavioural intention. Using a quantitative approach, data from 155 visitors were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that destination image positively influences MTEs and satisfaction but does not directly affect behavioural intention. Instead, behavioural intention is shaped through the mediating effects of MTEs and satisfaction, both of which are key drivers of tourists’ intention to revisit and recommend destinations. The findings emphasize that positive perceptions of safety and infrastructure must be translated into meaningful and memorable experiences to create value for tourists. The study provides strategic insights for policymakers and destination managers, highlighting the importance of shifting tourism development and marketing efforts from image-focused promotion to experience-oriented strategies supported by adequate infrastructure, in order to strengthen tourist loyalty, encourage positive word-of-mouth, and support sustainable tourism redistribution